Theme-Rheme Analysis and Thematic Progression in Joko Widodo’s Speech - Like Raskova Octaberlina; Afif Ikhwanul Muslimin (OKARA: Jurnal Bahasa dan Sastra, 2020)
Indonesia president, Mr. Joko Widodo, delivered a speech concerning some decisions related to social support and people's massive movements to stop the COVID-19 in Indonesia. Some unique functional grammar, namely theme-rheme and thematic progression, are found in his speech. The research focuses on analyzing the theme-rheme and the thematic progression (TP) types in Joko Widodo's speech both in the source language (SL) or Bahasa Indonesia and target language (TL) or English translation. It made a comparison to depict the differences and similarities between them. This study was a descriptive qualitative research method by taking the speech texts and their translation. The research results showed that the most frequently used theme in both SL and TL speech texts was the topical theme (66%). The second was the textual theme, and the least used was the interpersonal theme. Both SL and TL speech texts employed all thematic progression that shows the texts have been developed cohesively. However, the theme derived thematic progression becomes the most frequent TP as the speaker and translator used a single theme to develop another related theme in the next clause. This type of TP stated the different dominant types of TP used by other presidents' speech